Rozłóż wielomian w na czynniki:

c) w(x)=3[tex]x^{5}[/tex]+2[tex]x^{4}[/tex]-6[tex]x^{3}[/tex]-4[tex]x^{2}[/tex]-9x-6
d) w(x)=(7[tex]x^{4}[/tex]+14[tex]x^{3}[/tex]-21[tex]x^{2}[/tex])([tex]x^{5}[/tex]-4[tex]x^{3}[/tex]-[tex]x^{2}[/tex]+4)


Odpowiedź :

Odpowiedź:

c)

w(x)= x⁴(3x+2) -2x²(6x+2) -3(3x+2)= (x⁴-2x²-3)(3x+2)=(x+2)²(x-2)²(3x+2) bo

x²=t                 t²-2t-3=0           Δ=4+12=16        √Δ=4

t1=(2-4)/2=<0 = sprzeczne                t=(2+6)/2=4

x²=4                x=2       ∨   x=-2

d)

w(x)= 7x²(x²+2x-3)*x³(x²-4)-1(x²-4)=7x²(x²+2x-3)(x³-1)(x²-4)=

7x²(x+3)(x-1)(x-1)(x²+x+1)(x+2)(x-2)=7x²(x+3)(x-1)²(x²+x+1)(x+2)(x-2)

Δ=4+12=16          x1=(-2-4)/2=-3           x2=(-2+4)/2= 1

Szczegółowe wyjaśnienie:

wzory

a³-b³            i   a²-b²